The Educational and Psychological Problems of Distinguished Students: علم النفس (Journal of the College of Education for Women, 2020)
The present research aims at identifying the educational problems and psychological problems of distinguished students at the intermediate level. The research sample consists of (246) students who are randomly selected from four distinguished schools (2) in the Karkh\1 and (2) in the Rusafa\2.The researcher has constructed two scales for measuring the educational and psychological problems. She ensures the psychometric characteristics of the two scales. Alph-Cronbach and test-retest methodsare used to ensure reliability. Some statistical treatments are used to find out the aims of research. These treatments include the one-sample T-test, two independent samples T-test, and the Pearson correlation coefficient. The results show that the sample members do not have educational problems, while they suffer from psychological problems in a moderate degree. Furthermore, there are statistically significant differences in educational/psychological problems in general according to the gender variable in favor of males. The educational and psychological problems are arranged in descending order according to their percentage to identify the five most prominent educational problems as follows:The eighth problemweights(80)The sixth problem weights(68.67(The twelfth problem weights(68)The fourth problem weights(67.67)Sixteenth problem weights(66.33(The psychological problems are listed as follows:The twenty-sixth problem has reached (82.67 .(The eighteenth problem has reached (79.67(.The third problem has reached (78).The fifteenth problem has reached (77, 67).The eleventh problem has reached (76.33).The results show that there is a direct accelerated relationship between educational problems and psychological problems since the value of the correlation coefficient is (0.24).